Measurement of ultrasonic diaphragmatic motion - Chrysostomou, Christis; Loizou, Christos P.; Minas G., G.; Delibasis, Konstantinos K.; Pattichis, Constantinos S. (My University, 2015)
The motion characteristics of the diaphragmatic muscle may provide useful information about normal and abnormal diaphragmatic function and indicate diaphragmatic weakness. The objective of this paper was to introduce a simple system for the quantitative analysis of ultrasonic diaphragmatic motion. The measurements routinely carried out by the experts were computed and these include: (i) excursion, (ii) inspiration time (Tinsp) and (iii) cycle duration (Ttot). The system was evaluated on four simulated videos and one real video. Manual and automated measurements were very close. Further work in a larger number of videos is needed for validating the proposed method
Keywords: Diaphragm imaging; Physiology; Humans; Image processing; Ultrasonography; Video recording